UJI TEKNIS CROWN INDO JARWO TRANSPLANTER DI DESA TUYAT KECAMATAN LOLAK - Dai -; R. A. Rantung; F. Pangkerego (Universitas Sam Ratulangi, 2018)
ABSTRACT Generally, the processes of paddies planting in Lolak district are still using conventional systems, such as tegel planting, hambela and tabela. Those kinds of systems involve a lot of labor, take much time and high cost. In 2016, The Government of Lolak district through Department of Agriculture had helped the farmers by giving them a planting machine which is Crown Indo Jarwo, but unfortunately the farmers didn’t use it well. The purpose of this study was a technical test of Crown Indo Jarwo Transplanter, includes the uniformity of seeds planting from planter forks, field efficiency, calculating fuel consumption and analyzing the basic costs of planting. The methods that used in this study were experimental and dialysis methods in descriptive by planting paddies mechanically with Crown Indo Jarwo transplanter. This study also used 3 plots of paddy fields of the same size, 30 m x 11 m. The results of this study obtained the working capacity is 5,35 hours/ha, the fuel consumption is as much as 1.435 liters/hour, uniformity of seed plugging of 96.8%, theoretical field capacity and effective field capacity of 0.235 ha/hours and 0.187 ha/hour so that field efficiency is 79.74% and the cost of planting is Rp. 444,127,-/ Ha. Keywords: Indo Jarwo Transplanter, field efficiency